THE CONTRIBUTION OF DIGITAL CLASSROOM MEDIA TO STUDENTS’ LEARNING ENTHUSIASM - Kholid (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2026)
This study aimed to examine the contribution of digital classroom media to students’ learning enthusiasm in the teaching and learning process. The research employed a quantitative approach using a correlational research design to investigate the relationship between digital classroom media and students’ learning enthusiasm. The participants of this study consisted of 60 secondary school students selected through purposive sampling techniques. Data were collected using a questionnaire that measured students’ perceptions of digital classroom media and their enthusiasm toward learning activities. The collected data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that students had positive perceptions toward the use of digital classroom media in classroom instruction. Students considered digital learning tools more interactive, attractive, and effective in supporting their understanding of learning materials. The results also showed that students demonstrated higher levels of attention, participation, curiosity, and enthusiasm during learning activities involving digital media. Furthermore, the regression analysis indicated that digital classroom media had a positive and significant contribution to students’ learning enthusiasm. The significance value obtained was lower than 0.05, indicating that the alternative hypothesis was accepted. The study concluded that digital classroom media play an important role in creating engaging and motivating learning environments. The integration of technology-based instructional media can improve students’ enthusiasm and encourage active participation in classroom learning activities. Therefore, teachers are encouraged to implement innovative digital classroom media to support effective and student-centered learning processes. Future studies are recommended to involve larger populations and additional variables to obtain more comprehensive findings regarding the role of digital classroom media in education.